2012
DOI: 10.1007/s00403-012-1217-5
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium sulfate protects fetal skin from intrauterine ischemia reperfusion injury

Abstract: Intrauterine ischemia-reperfusion (I/R) injury in fetus occurs with multifactorial pathogenesis and results with multiorgan injury including skin. Magnesium has widespread use in obstetric practice. Inn addition to magnesium's tocolytic and neuroprotective properties, it also has free radical reducing effects. The aim of the present study was to demonstrate whether magnesium sulfate could have protective effect on fetal rat skin in intrauterine ischemia-reperfusion (I/R) injury. Fetal skin ischemia was induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“… 30 Kaptanoglu et al demonstrated that administration of magnesium reduced the I/R injury on fetal rat skin. 31 A free radical reducing effect of magnesium in a coronary occlusion reperfusion model was demonstrated by Garcia et al 32 It was also demonstrated that magnesium reduces the lactate and MDA levels after cerebral ischemia. 33 It was shown that application of Lomodex–MgSO 4 prior to detorsion increases semen quality and fertility.…”
Section: Discussionmentioning
confidence: 89%
“… 30 Kaptanoglu et al demonstrated that administration of magnesium reduced the I/R injury on fetal rat skin. 31 A free radical reducing effect of magnesium in a coronary occlusion reperfusion model was demonstrated by Garcia et al 32 It was also demonstrated that magnesium reduces the lactate and MDA levels after cerebral ischemia. 33 It was shown that application of Lomodex–MgSO 4 prior to detorsion increases semen quality and fertility.…”
Section: Discussionmentioning
confidence: 89%
“…It was suggested that magnesium, an L-type calcium channel blocker, may be effective in preventing IR damage by reducing calcium overload related to tissue damage [6][7][8][9]. There are studies showing that magnesium sulfate is used at different doses in different organ irradiation therapies [6][7][8]20]. In our study, magnesium sulfate was administered 200 mg/kg intraperitoneally 20 minutes before ischemia.…”
Section: Discussionmentioning
confidence: 94%
“…Magnesium sulfate inhibits endotoxin-dependent inflammatory molecule up-regulation. It was suggested that magnesium, an L-type calcium channel blocker, may be effective in preventing IR damage by reducing calcium overload related to tissue damage [6][7][8][9]. There are studies showing that magnesium sulfate is used at different doses in different organ irradiation therapies [6][7][8]20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its microbiome and its physical, chemical, and immune barriers constitute an interactive network that protects individuals from external harm [ 21 ]. The 5 elements tested in the current study strongly influence the functions of skin, with effects on wound healing [ 22 , 23 ], scar formation and contraction [ 24 ], microvasculature blood flow [ 25 , 26 ], and immune function [ 27 ]. A deficiency of these 5 elements may cause skin lesions [ 28 – 30 ], while supplementation may lead to improved skin functions [ 21 , 31 ].…”
Section: Discussionmentioning
confidence: 99%